Problem Realisasi Kebijakan Smart City di Indonesia: Kasus Kota Bandar Lampung - Dwi Wahyu Handayani; Syafarudin Syafarudin; Lilih Muflihah (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2021)
This article examines government capacity in realizing smart city with a special reference to Bandar Lampung City, Indonesia, especially in the aspects of smart governance and smart people (social and human capital). The method used was qualitative with interviews and survey as data collection techniques. Using the concept of smart city and governance, this article shows that in realizing smart governance, Bandar Lampung government tended to focus on infrastructure development, which did fully involve the development of the quality of human resources and social capital, and was not based on community problems and the state mission of education and health development. The infrastructure development did not fully provide people with a good quality of administration, education and health services, and neglected social and environmental issues. These problems with smart governance caused the low public trust to government, which was an important social capital of the working of smart people.